One health conceptual framework: antimicrobial resistance - Mantovani, Alberto (Henry Stewart Talks, 2025)
Antimicrobial resistance (AMR), One health (OH), Microbiology, Epidemiology, AMR through food chain, Preventive measures for AMR transmission, Food safety, Environmental reservoirs of AMR, OH and AMR in European Union -Veterinary medicine, Animal health, Ecosystem